RED LIGHT PROTOBIOMODULATION – THE WAY TO STAY YOUNG AND CURE DISEASE – A REVIEW OF THE LITERATURE - Aleksandra Magdalena Furczyńska,; Patryk Kowalczyk,; Filip Bracichowicz,; Aleksandra Gęsińska,; Hanna Paszkiewicz,; Kamil Nowak,; Igor Winogrodzki,; Bartłomiej Trzciński,; Alicja Stryczek-Schlusche,; Oliwia Gugała, (International Journal of Innovative Technologies in Social Science, 2025)
Red light and infrared light are key in application of Low level laser therapy and Photodynamic therapy. Their use ranges from wound healing and acne therapy to skin rejuvenation and treatment of androgenic alopecia. Many clinical studies have proven its effectiveness and compatibility with other treatment forms.Background: Visible red light (RL, 620-700 nm) and the near-infrared (NIR, 700-1440 nm) are key in process called photobiomodulation (PBM) in which absorbed light causes physiologicaleffects in the skin at cellular level. Light of this wavelength penetrates into the dermis and interacts with melanocytes, as well as fibroblasts, endothelial cells, and immune cells residing within the dermal layer. Changes in biological processes resulting from this include: increased RNA and protein synthesis, and increases in oxygen consumption, membrane potential, and NADH and ATP synthesis. Observed physiological effects range from enhancement in cell signaling and growth factor synthesis to reduction of oxidative stress and decrease in IL-1β, IL-10, and TNF-α levels.Aim: The aim of this article is to present different ways red light therapy has been utilized in medical fields and the results accomplished with it.